Stability-Indicating UHPLC Method for the Determination of Desvenlafaxine: Application to Degradation Kinetics (Dhaka University Journal of Pharmaceutical Sciences, 2021)
This study was aimed to investigate the degradation behavior and physicochemical stability of desvenlafaxine using reversed-phase ultra-high-performance liquid chromatography (RP-UHPLC) system. The chromatogram was developed on Eclipse XDB-C8 column (150 x 4.6 mm, 5μm). The eluents were monitored through a photo diode array plus (PDA+) detector at 210 nm using an isocratic method with a flow rate of 1.5 ml/min. Mobile phase composition was 30:70 v/v mixture of 0.1 % trifluoroacetic acid (TFA) in water and methanol. Forced degradation studies were performed on drug substance of desvenlafaxine as per International Conference on Harmonization (ICH) prescribed stressed conditions (Q1A(R2) and Q1B) using hydrolytic (acidic, basic, and neutral), oxidative and photolytic methods. The drug substance was found highly labile to acidic (0.5 N hydrochloric acid, 18.65 % degradation in 2 hours at 70°C), basic (1.0 N sodium hydroxide, 11.01 % degradation in 12 hours at 70°C) and oxidative (3 % hydrogen peroxide, 17.05 % degradation in 2 hours at 50°C) stressed conditions, but a great resistance was observed towards dry heat (maximum degradation 0.27 % in 10 days from ambient to higher temperature, 80°C), moist heat (maximum degradation 0.25 % in 2 hours at 80°C and 75 % relative humidity) as well as in photolytic degradation (maximum degradation 0.23 % in 10 days at UV light of 315 - 400 nm). A pseudo-first order kinetic was followed in acidic, basic and peroxide degradation methods which paved a way to calculate the half-life of the drug substance desvenlafaxine under ICH mentioned stressed conditions. The results were also statistically analyzed and the % RSD values were compared with recommended guidelines.Dhaka Univ. J. Pharm. Sci. 20(2): 167-176, 2021 (December)